KINERJA APARATUR PADA DINAS BINA MARGA PROVISI SULAWESI TENGAH - Riny, Riny (Katalogis, 2016)
Performance Analysis Apparatus At the Highways Department, Central Sulawesi Province". The purpose of this study was to determine the performance Apparatus At the Highways Department, Central Sulawesi Province. This type of research with qualitative approach derived from the results of in-depth interviews. The location of research in the Department of Highways Office of Central Sulawesi province. The informants of five (5) employees with data sources include primary data and secondary data and data collection through interviews, observation, and documentation. Analysis of the data by using interactive data analysis model. The results showed a good enough motivation obtained by the employees either through from the head or from among the employees motivate each other. Ability aspect, the employees are less well in understanding the task of making it less able to work optimally. And the opportunity aspect, the employees have not been uniformly given the flexibility in planning and carrying out its duties and responsibilities and be given the opportunity to participate in any implementation of the activities as well as training and education in the form of technical guidance to increase their capacity and experience.